Ipriflavone ameliorates intervertebral disc degeneration by inhibiting osteoporosis of vertebral body and pyroptosis of the nucleus pulposus in instability of lumbar spine and diabetic mice - Sun, Qi; Zhang, Hai-Jing; Wang, Hui; Ji, Gang; Zhao, Ya-Heng; Li, Gao-Cen; Guo, Shao-Shi; Lin, Lu-Feng; Jin, Yu-Jie; Zhang, Xue-Li; Nan, Xin-Yu; Liu, Chang-Cheng; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundDiabetes mellitus (DM) is a chronic metabolic disease, which can not only induce osteoporosis but also accelerate intervertebral disc degeneration (IVDD). Ipriflavone (IP), as a derivative of isoflavones, can not only control the level of blood glucose, but also improve the regulation of osteoporosis and cartilage extracellular matrix metabolism. However, there is no study on whether IP can effectively improve DM with IVDD.MethodsSixty healthy female C57BL/6J mice were randomly assigned into five groups (Sham, Instability of lumbar spine (ILS), streptozotocin (STZ), ILS + STZ and ILS + STZ + IP groups; 12 per group). The body weight, fasting glucose and blood insulin levels were evaluated in each group of mice. The pathology of DM with IVDD was assessed by Micro-CT (μCT), Van Gieson (VG) staining, Alcian blue (Ab) staining, immunohistochemistry, Western blot and real-time polymerase chain reaction (RT-PCR).ResultsIP significantly lowed fasting blood glucose and blood insulin levels. Histomorphological analysis revealed that IVDD was significantly exacerbated by the coexistence of ILS and DM, and markedly alleviated by IP. In details, IP markedly improved osteoporosis and microarchitecture of EP and vertebrae. Furthermore, IP ameliorated the cartilage extracellular matrix degradation, significantly increased Aggrecan and Col II expression and decreased the expression of MMP13 and ADAMTS-4. Moreover, IP inhibited EP sclerosis and NP pyroptosis by decreasing Runx2, Osterix, NLRP3, ASC, N-GSDMD and caspase1 expression.ConclusionThe coexistence of ILS and DM further aggravates abnormal metabolic pathology and IVDD, which could be retarded by IP, suggesting that IP may be a potential therapeutic target for amelioration of the progression of DM with IVDD.